2020
DOI: 10.24259/fs.v4i1.8486
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Changes in Coastal Mangrove Extents Using Multi-Temporal Satellite Data in Selected Communes, Hai Phong City, Vietnam

Abstract: Mangrove forests are important and known as one of the most productive ecosystems in the tropics. They reduce the impacts of extreme events, provide important breeding grounds for aquatic species and build the resilience of ecosystem-dependent coastal communities. On the contrary, they are also known as one of the most threatened and vulnerable ecosystems worldwide, which have experienced a dramatic decline due to extensive coastal development during the last half-century. Remote sensing techniques have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
2
20
0
2
Order By: Relevance
“…It could generate accurate, reliable, and efficient spatial information important for mangrove monitoring and for examining the ecosystem response to anthropogenic drivers and environmental changes [26,27]. The findings from this study may be used by the subnational government for implementing low carbon development under the land sector, including conservation-based management improvement, and would also be useful to guide future restoration efforts [28]. This is in line with the current national climate policy interests, in which the Government of Indonesia will be incorporating the mangrove ecosystem as part of the nature-based climate solution from the land-use sector.…”
Section: Introductionmentioning
confidence: 95%
“…It could generate accurate, reliable, and efficient spatial information important for mangrove monitoring and for examining the ecosystem response to anthropogenic drivers and environmental changes [26,27]. The findings from this study may be used by the subnational government for implementing low carbon development under the land sector, including conservation-based management improvement, and would also be useful to guide future restoration efforts [28]. This is in line with the current national climate policy interests, in which the Government of Indonesia will be incorporating the mangrove ecosystem as part of the nature-based climate solution from the land-use sector.…”
Section: Introductionmentioning
confidence: 95%
“…This coefficient indicates that there is a substantial agreement between data collected from the field survey and the results-derived Landsat-8 image classification (Malarvizhi et al, 2016;Dan et al, 2016). During accuracy assessments, mapping accuracy might be affected by possible mixed-pixel issues, tidal regime and cloud cover percentage (Hai-Hoa et al, 2020b). However, the overall accuracy assessment with 80.0% has confirmed that the land use and land cover mapping by Landsat-8 are applicable over the coasts of Hai Ha and Mong Cai, Quang Ninh Province (Hai-Hoa et al, 2020a, 2020b.…”
Section: Accuracy Assessments Of Land Use and Land Cover Mappingmentioning
confidence: 84%
“…Gain bias correction scattering effects and corrections of the sun angle are necessary and mangrove cover analysis is conducted (Norjamaki and Tokola, 2007;Gupta et al, 2018;Hai-Hoa et al, 2020a). Radiometric calibration of Landsat-8 bands was applied to convert digital number values into top of the atmosphere spectral radiance (TOA), then bands were converted to TOA planetary reflectance (Chander et al, 2009;Gupta et al, 2018;Hai-Hoa et al, 2020b). Atmospheric and radiometric corrections were all employed to remove errors and increase accuracies by using the Spatial Analyst Tools in ArcGIS 10.6.…”
Section: Data Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations